Answer:
Step-by-step explanation:
So we would have to multiply the "2x - 8" by 5 each resulting in 10x - 40 + 15. Then we subtract which results in 10x - 25 = - 15. We add 25 to 25 and 15 resulting in 10x = 10. We divide each by 10 which results in x = 1.
Step-by-step explanation:
the introduction of a fraction tells us that we are dealing with multiplications, and therefore a geometric sequence (where every new term is created by multiplying the previous term by a constant factor, the ratio r).
I think your teacher made a mistake, or you made one when typing the question in here.
there is no factor r that creates
15×r = 9
and
9×r = 5/27
it would mean that
15 × r² = 5/27
r² = 5/27 / 15 = 5/27 × 1/15 = 5/405 = 1/81
r = 1/9
but 15 × 1/9 = 5 × 1/3 = 5/3 is NOT 9
and 9 × 1/9 = 9/9 = 1 is NOT 5/27
so, this can't be right.
on the other hand
15 × r = 9
r = 9/15 = 3/5
and then
9 × 3/5 = 27/5
so, either the sequence should have been
15, 5/3, 5/27
or (and I suspect this to be true)
15, 9, 27/5
under that assumption we have
s1 = 15
r = 3/5
sn = sn-1 × r = s1 × r^(n-1) = 15 × (3/5)^(n-1)
s10 = 15 × (3/5)⁹ = 15 × 19683/1953125 =
= 3 × 19683/390625 = 59049/390625 =
= 0.15116544 ≈ 0.151
Answer:
Step-by-step explanation:
Y=x+1.25
Square pyramid is the answer to your question
Answer:
f(x) = 10x + 13
Function f(7) = 83
Step-by-step explanation:
y = 10x + 13
f(x) = 10x + 13
Function f(7) = 10(7) + 13
Function f(7) = 83